The Spectrum of Mapping Ideals of Type Variable Exponent Function Space of Complex Variables with Some Applications - Awad A. Bakery; Mustafa M. Mohammed (Journal of Function Spaces)
The topological and geometric behaviors of the variable exponent formal power series space, as well as the prequasi-ideal construction by s-numbers and this function space of complex variables, are investigated in this article. Upper bounds for s-numbers of infinite series of the weighted nth power forward and backward shift operator on this function space are being investigated, with applications to some entire functions.